Energy and exergy analysis of a bidirectional solar thermoelectric generator combining thermal energy storage - Montero, Francisco J.; Lamba, Ravita; Singh, Sarveshwar; Jahn, Wolfram; Chen, Wei-Hsin (Frontiers in Energy Research, 2023)
In this paper, energy and exergy analysis of a bidirectional solar thermoelectric generator (STEG) coupled to a latent heat storage and cooling system (LHSCS) has been carried out.The effect of various parameters of LHSCS on energy and exergy efficiencies of STEG have been analysed under climatic conditions of Chile's Atacama Desert. It is found that the most relevant design parameter to improve the energy and exergy efficiencies of the thermoelectric generator (TEG) is the container insulation, followed by heat sink at the TEG hot side, fin thickness and the aspect ratio of the container. The results showed that an optimally designed insulation container can improve the energy and exergy efficiencies of LHSCS by 30% and 200%, respectively, and the TEG conversion efficiency by 30% during nighttime. Further, inclusion of heat sink at TEG hot side during reverse operation of TEG at night can improve the TEG efficiency by 20%. The optimal fin thickness can improve the TEG conversion efficiency by 20% during the night and LHSCS energy and exergy efficiencies by 30% and 23%, respectively. The container geometry should have higher aspect ratios. This study may help in optimal design of LHSCS for solar energy conversion applications in the desert locations.